Magnetic Nanoparticle Systems for Nanomedicine—A Materials Science Perspective - Socoliuc, Vlad; Peddis, Davide; Petrenko, Viktor I.; Avdeev, Mikhail V.; Susan-Resiga, Daniela; Szabó, Tamas; Turcu, Rodica; Tombácz, Etelka; Vékás, Ladislau (Magnetochemistry, 2020)
Iron oxide nanoparticles are the basic components of the most promising magneto-responsive systems for nanomedicine, ranging from drug delivery and imaging to hyperthermia cancer treatment, as well as to rapid point-of-care diagnostic systems with magnetic nanoparticles. Advanced synthesis procedures of single- and multi-core iron-oxide nanoparticles with high magnetic moment and well-defined size and shape, being designed to simultaneously fulfill multiple biomedical functionalities, have been thoroughly evaluated. The review summarizes recent results in manufacturing novel magnetic nanoparticle systems, as well as the use of proper characterization methods that are relevant to the magneto-responsive nature, size range, surface chemistry, structuring behavior, and exploitation conditions of magnetic nanosystems. These refer to particle size, size distribution and aggregation characteristics, zeta potential/surface charge, surface coating, functionalization and catalytic activity, morphology (shape, surface area, surface topology, crystallinity), solubility and stability (e.g., solubility in biological fluids, stability on storage), as well as to DC and AC magnetic properties, particle agglomerates formation, and flow behavior under applied magnetic field (magnetorheology).